(untitled) (Itinera, 2025)
Aesthetic and ecological poetics of biophilic design. The regenerative power of nature in urban areas Nowadays alarming situation which concerns the compromise of life on the planet Earth places us in front of a predicted danger of sixth mass extinction just some decades ago. Serious environmental and biodiversity crisis urgently require decisive actions to guarantee next future. Beyond a sustainable commitment programmed by international organizations, is necessary to restore the relationship with nature awakening authentic original relationship called “biophilia”. This last consists in humankind’s innate biological connection with nature which can lead to ecological awareness including preservation of life. One of the effective way which aims awakening this ancestral emotional connection with environment and other living forms and at the same time improving urban environment and increasing the biodiversity in urban areas is an innovative concept of architecture based on biophilic design. Urban areas that follow this approach help to human improve the quality of life, interpersonal relationships, general health and promoting respect of life. Cities containing natural elements are characterized by positive connection between human, environment and other living forms. The acquisition of ecological awareness developing bioethics and naturalistic intelligence is the first step to try safeguard life of the Earth.